MATHEMATICAL PROGRAMMING AND ACCOUNTING APPROACHES TO INCREMENTAL COST ANALYSIS. - Dopuch, Nicholas (The Accounting Review, 1963)
In recent years there has been a rapid growth in the application of mathematical programming techniques to the solution of particular types of managerial problems. This increased use of programming techniques should be of interest to accountants for at least two general reasons: there is a definite similarity in the underlying approaches of programming and accounting to a certain type of managerial problems and the application of programming techniques by managements of firms will have a rowing impact on the accountant's function of supplying data used in making decisions concerning the allocation of resources and also the data needed for the control and evaluation of these decisions. The manager of a firm is generally faced with two broad categories of decision-making problems. First he must determine the proper amounts and types of resources which are necessary for the achievement of the organization's objective or objectives. The implementation and the evaluation of linear programming solutions seem to require more work in the development of an analysis of standard cost systems since these systems traditionally have not seemed to be explicitly related to the current planning governing the uses of committed resources.